2007
DOI: 10.1111/j.1574-6941.2007.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-strand displacement and identification of single nucleotide polymorphisms as markers of genotypic variation of Pasteuria penetrans biotypes infecting root-knot nematodes

Abstract: Pasteuria species are endospore-forming obligate bacterial parasites of soil-inhabiting nematodes and water-inhabiting cladocerans, e.g. water fleas, and are closely related to Bacillus spp. by 16S rRNA gene sequence. As naturally occurring bacteria, biotypes of Pasteuria penetrans are attractive candidates for the biocontrol of various Meloidogyne spp. (root-knot nematodes). Failure to culture these bacteria outside their hosts has prevented isolation of genomic DNA in quantities sufficient for identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…; Nong et al . ). However, in this study, they appeared to be insufficient to resolve populations at the intraspecies level as observed previously by Mauchline et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Nong et al . ). However, in this study, they appeared to be insufficient to resolve populations at the intraspecies level as observed previously by Mauchline et al .…”
Section: Discussionmentioning
confidence: 97%
“…They are distributed throughout the genomes of closely related Bacillus spp. (27) and so should provide a clear understanding of protein-encoding gene variation on a global scale in P. penetrans. We also examine equivalent genes in two other related species of Pasteuria to improve the classification of this family.…”
mentioning
confidence: 99%
“…It is thus ideal for unculturable bacteria. Nong et al (2007) applied this approach to females of M. incognita infected with vegetative cells of P. penetrans. They found that 2,000 vegetative Pasteuria cells were sufficient to give complete genome coverage of the MDA-amplified template following PCR with specific primers.…”
Section: S Rrna Gene Fragmentsmentioning
confidence: 99%